Effect of Composition of HPAM/Chromium(III) Acetate Gels on Delayed Gelation Time. Issue 6 (2nd June 2016) - Sun, Feifei; Lin, Meiqin; Dong, Zhaoxia; Zhu, Daoyi; Wang, Shuang Long; Yang, Jie
Abstract : A delayed crosslinking system employed with hydrolyzed polyacrylamide (HPAM) and chromium acetate was developed for high profile control in low-temperature reservoirs. The crosslinking system formed strong gel at polymer concentration range of 3000–5000 mg/L, and the gelation time was delayed to 8–30 days, which offered the crosslinking system enough time to flow into deep water-producing zones and plug large pore paths, forcing follow-up fluids to enter low-permeability layer and reduce disproportionate permeability. The effect of polymer hydrolysis degree, polymer concentration, pH, and crosslinker concentration on delaying gelation time was evaluated using bottle testing. Meanwhile, sand-packed tube displacement experiments revealed the plugging performance of delayed crosslinking system. According to Fourier transform infrared spectroscopy (FTIR) analysis, as well as crosslinking mechanism between polymer and chromium acetate, the delayed mechanism of crosslinked system demonstrated that due to stronger affinity of acetate complexes as a ligand, its substitution in situ by carboxylate group of polyacrylamide slowed down the initial rate-determining step of crosslinking reaction. GRAPHICAL ABSTRACT: